Dampak Profesionalisme, Independensi, dan Etika Profesi Terhadap Kinerja Auditor Pada KAP Di Semarang - Saifudin Saifudin; Setia Dewi Ayuningtias (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2020)
The role of the accounting profession is very important in providing reliable financial information for interested parties, it requires the skills of professional accountants. This can be seen through the level of professionalism, independence, and the application of professional ethics. So, this study aims to examine the effect of professionalism, independence, and professional ethics on the performance of auditors at the Public Accounting Firm in Semarang City. This type of research is quantitative research. The population used is all auditors at the Public Accounting Firm in Semarang City who is registered at the Indonesian Institute of Certified Public Accountants. Sampling in this study using a purposive sampling method. The data sources used are primary and secondary data. The target respondents of this study were 60 respondents, but the respondent's data that could be processed were 53 respondents' answers. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that professionalism has an effect on auditor performance, independence has an effect on auditor performance, and professional ethics has an effect on auditor performance